Integration of the Indonesian Islamic Stock Index: Evidence from Developed and Developing Countries - Budiandru Budiandru; Deni Nuryadin (Ekonomi Syariah IAIN Kudus, 2022)
Globalization is changing the world's economic and financial systems are increasingly integrated. Globalization can also trigger shocks to the Islamic stock market and reduce diversification benefits for investors. This study aims to analyze the integration of the Indonesian Islamic stock index with the Islamic stock index of developed and developing countries. Using a vector error correction model and daily data from 2012 to 2021, which reached 2088, the observations reveal that the Indonesian Islamic stock index is integrated with the Islamic stock index of developed and developing countries. The Indonesian Islamic stock index responded positively and negatively to the developed and developing Islamic stock index. Japan has the most significant contribution in influencing Indonesia's Islamic stock index. Indonesia's Islamic stock index needs to prepare various alternative strategies in dealing with shocks from developed and developing country Islamic stock indexes.